A Geoarchaeological Study of the Middle and Upper Pleistocene Levels at Canteen Kopje, Northern Cape Province, South Africa. Issue 4 (25th January 2016) - Lotter, Matt G.; Gibbon, Ryan J.; Kuman, Kathleen; Leader, George M.; Forssman, Tim; Granger, Darryl E.
Abstract : Canteen Kopje, situated in the Northern Cape Province of South Africa, has two main archaeological deposits: alluvial gravels and a mantle of overlying fine sediments known locally as the "Hutton Sands." This paper focuses on the fine sediments, the three industries contained within them, and the interface with the underlying gravels in an attempt to clarify their formation and transformation. A Fauresmith assemblage is found at this interface; it is thus crucial to understand the processes of deposition and modification at this poorly understood boundary. The methods used in this study involved the analysis of artifact depositional (dip and orientation) and spatial data, artifact condition, raw materials, and assemblage size profiles. Data presented document the mixing between the lowest levels of the fine sediments and the underlying alluvial gravels. This study thus provides important contextual information for the Fauresmith industry at Canteen Kopje.